2019
DOI: 10.3389/fnmol.2019.00264
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment With Fasudil Prevents Neomycin-Induced Hair Cell Damage by Reducing the Accumulation of Reactive Oxygen Species

Abstract: Ototoxic drug-induced hair cell (HC) damage is one of the main causes of sensorineural hearing loss, which is one of the most common sensory disorders in humans. Aminoglycoside antibiotics are common ototoxic drugs, and these can cause the accumulation of intracellular oxygen free radicals and lead to apoptosis in HCs. Fasudil is a Rho kinase inhibitor and vasodilator that has been widely used in the clinic and has been shown to have neuroprotective effects. However, the possible application of fasudil in prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…HCs in the cochlea play a critical role in converting mechanical sound waves into neural signals for hearing [19][20][21]. Most hearing loss induced by noise, different ototoxic drugs, inflammation, or aging is caused by the HC damage [22][23][24][25][26][27][28][29]. Ribbon synapses are vital structures between inner HC and SGNs, which are the primary synaptic structures in the sound conduction pathway and play an important role in sound signal transmission [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…HCs in the cochlea play a critical role in converting mechanical sound waves into neural signals for hearing [19][20][21]. Most hearing loss induced by noise, different ototoxic drugs, inflammation, or aging is caused by the HC damage [22][23][24][25][26][27][28][29]. Ribbon synapses are vital structures between inner HC and SGNs, which are the primary synaptic structures in the sound conduction pathway and play an important role in sound signal transmission [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the hearing loss patients have the same pathological features in common such as the HC loss and the decreased number of SGNs [11,12]. Ototoxic insult to the sensory HCs causes hair cell death, which is mainly due to the exposure to loud noise, use of aminoglycosides or chemotherapy regimens, viral infections, biological aging, and genetically inherited disorders [13][14][15][16][17][18][19][20]. The drug-induced damage also promotes the reduction of specialized synaptic structures between IHCs and SGNs followed by the later degeneration of SGN [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Hair cells in the cochlea play a critical role in converting mechanical sound waves into neural signals for hearing [3][4][5]. Previous studies using mouse models showed that acoustic injury of the auditory system is caused by multiple factors, and most of the hearing loss induced by noise, different ototoxic drugs, infection, or aging are caused by the hair cells damage [6][7][8][9][10][11][12][13]. Impulse noise (>140 dB SPL) causes hearing loss primarily through mechanical damage of hair cells [14], while steady noise causes metabolic damage of hair cells [15].…”
Section: Introductionmentioning
confidence: 99%